KEBERADAAN BADAN USAHA MILIK DESA (BUMDES) HUNTU SELATAN KECAMATAN BULANGO SELATAN - Salmia S. Abaidata; Umar Sako Baderan; Nur Eng Mokodompit (Akademika : Jurnal Ilmiah Media Publikasi Ilmu Pengetahuan dan Teknologi, 2024)
Village-Owned Enterprises (BUMDes) are one of the instruments established by the government to improve rural community economies through independent and sustainable management of local potential. The existence of BUMDes is expected to encourage community welfare and strengthen rural economic development. This study aims to determine the existence and role of BUMDes in Huntu Selatan Village, South Bulango District, in supporting community economic improvement. This research employed a qualitative approach using observation, interviews, and documentation techniques for data collection. The results show that the existence of BUMDes Huntu Selatan has had a positive impact on improving the community’s economy, particularly through business capital loan programs for small communities. Until 2019, the funds managed by BUMDes reached Rp282,000,000 with 78 customers. The existence of BUMDes has helped the community develop productive businesses such as grocery stores, cake production, food stalls, and other small businesses. However, several obstacles were still found, including delays in loan repayments and limited business unit development. Therefore, improving management quality, strengthening human resources, and developing business units are necessary to ensure the sustainability of BUMDes and increase its benefits for the rural community.